ANALISIS KONTRIBUSI PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR (PKB&BBNKB) TERHADAP PENDAPATAN ASLI DAERAH DI SAMSAT KABUPATEN GORONTALO - Radjak, Lukfiah Irwan; Yusuf, Fitria Melynsyah; Iyonu, Mentari Ariesta; Ayuba, Bambang Sevtian (JSAP : Journal Syariah and Accounting Public, 2024)
This research aims to measure the contribution of PKB & BBNKB in Samsat Gorontalo Regency to the Local Revenue in Gorontalo Province. This research used quantitative description. Data collection techniques are done through observation, data collection, and documentation. Based on the results of the research that has been done and the description of the discussion, it can be concluded that the contribution of PKB & BBNKB to PAD at Samsat Gorontalo Regency for the last four years is in the category of less, after calculating the average contribution of PKB & BBNKB to PAD is only 15.9%, this refers to the classification of contribution criteria according to the Ministry of Home Affairs No. 690.900.327. 1996. With a growth rate in 2019 of 14%, then in 2020, the growth rate of PKB & BBNKB decreased by 22%. In 2021, the growth rate of PKB & BBKB increased by 22%, and in 2022 only increased by 2%. With an average increase in the realization of PKB & BBNKB revenue at Samsat Gorontalo Regency of 4%, it is categorized as unsuccessful when referring to the Domestic Decree Number 13 of 2006 concerning Guidelines for Performance Assessment of Regional Companies.